2019
DOI: 10.1016/j.yhbeh.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment and testosterone reactivity: Fathers' avoidance predicts changes in testosterone during the strange situation procedure

Abstract: We assessed parents' testosterone reactivity to the Strange Situation Procedure (SSP), a moderately stressful parent-infant interaction task that pulls for parental nurturance and caregiving behavior. Parents (146 mothers, 154 fathers) interacted with their 1-year-old infants, and saliva samples were obtained pre-and post-task to assess changes in testosterone. We examined whether testosterone reactivity differed between mothers and fathers, the extent to which parents' characteristic approaches to closeness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Our study already indicated that highereducated fathers had lower CORT during an interaction with their toddler (see Table 3). Other studies, for example, point in the direction of romantic relationship quality and adult attachment orientation as factors that are associated with individual differences in parental T concentrations during pregnancy and parent-infant interactions (Chin et al, 2020;Edelstein et al, 2019). Such investigations are important in unravelling the hormonal bases of human parental care.…”
Section: Discussionmentioning
confidence: 99%
“…Our study already indicated that highereducated fathers had lower CORT during an interaction with their toddler (see Table 3). Other studies, for example, point in the direction of romantic relationship quality and adult attachment orientation as factors that are associated with individual differences in parental T concentrations during pregnancy and parent-infant interactions (Chin et al, 2020;Edelstein et al, 2019). Such investigations are important in unravelling the hormonal bases of human parental care.…”
Section: Discussionmentioning
confidence: 99%
“…There are limitations to the present study that merit attention. As we have discussed in past work from this study, our sample sizes of fathers were relatively small compared to some studies of paternal psychobiology in industrialized settings in more highly populated societies 72,[79][80][81][82] . However, we also note that our pooled analyses (n = 45) and BaYaka sample size (n = 29) compare favorably to other recent work in this area 25,72 , especially research in similar societies 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from this study have also focused on hormonal variation across parents and infants in the 12-month laboratory visit, including patterns of infants' cortisol responses based on the security of their attachment relationships with both fathers and mothers (Kuo et al, 2019), individual variation in fathers' testosterone across the visit and associations with fathering behaviors during fatherinfant interactions (Kuo et al, 2016), and parents testosterone reactivity during parent-infant interaction related to parents' adult attachment orientation (Edelstein et al, 2019). The current report builds on these previous studies by investigating cortisol interdependence and attunement between mothers and infants, and then attempting to replicate these findings with fathers and infants.…”
Section: Participantsmentioning
confidence: 99%